Refeeding with Free Lactose Milk ( A1 - 110 Nestle) in Children Suffering from Gastroenteritis and Dehydration - Suharjono Suharjono; Sunoto Sunoto; Aswitha Boediarso; Hentyanto Hendardji; Soegiharto Soegiharto (Paediatrica Indonesiana, 1975)
Forty one infants suffering from diarrhoea hospitalized in the Department of Child Health, Medical School, University of lndonesia/Dr. Tjipto Mangunkusumo General Hospital, Jakarta, from August 15, 1973 to January 15, 1974 were refed with "free lactose milk".The result is as follows :1. From the point of view of increase of body weight:27 (65.8 %) out of 41 cases were excellent.2 ( 4.9 %) out of 41 cases were good.12 (29.3 %) out of 41 cases were poor.2. From the point of view of stopping the diarrhoea :25 (60.9 %) out of 41 cases were excellent.10 (24.5 %) out of 41 was good.6 (14.6 %) out of 41 cases were poor.